Effects of Guanidinium Addition to CH3NH3PbI3 Perovskite Solar Cells Inserted with Decaphenylpentasilane - Iori Ono; Takeo Oku; Atsushi Suzuki; Masanobu Okita; Sakiko Fukunishi; Tomoharu Tachikawa; Tomoya Hasegawa (Chemistry Proceedings, 2022)
Effects of addition of guanidinium [C(NH2)3; GA] on MAPbI3 perovskite solar cells fabricated at a high temperature of 190 °C in atmospheric air were investigated on the photovoltaic properties and first principles calculations. The addition of guanidinium iodide and the insertion of decaphenylpentasilane between the perovskite and hole transport layer improved the external quantum efficiency and short-circuit current density, and the conversion efficiencies were stable after 1 month. First principles calculations on the density of states and band structures showed reduction of the total energy by the GA addition and the effectiveness of the nitrogen atoms in GA.